Need for Rectal Biopsy for Childhood Constipation Predicts Severity of Illness and Need for Laxatives. Issue 6 (June 2016) - Tran, Khoa; Staller, Kyle; Macklin, Eric; Goldstein, Allan; Belkind-Gerson, Jaime; Kuo, Braden
ABSTRACT: Objectives: This study aimed to examine the long-term clinical outcomes of children with severe constipation, as defined by need for rectal biopsy (RB), and to determine which baseline characteristics were predictors of successful outcome. Methods: Children with severe constipation who underwent RB for evaluation of Hirschsprung disease at a tertiary medical center were eligible. A cohort of children with constipation without a history of RB served as controls (matched 2:1 by sex and age). Retrospective chart review of clinic visits was performed at baseline, 3, 6, 12, 18, and 24 months. Successful clinical outcomes were defined as ≥3 bowel movements weekly for ≥4 weeks, with ≤2 fecal incontinence episodes monthly, irrespective of laxative use. Results: A total of 175 RB children (90 boys, mean age: 6.7 years) were matched to 350 controls. Mean duration of constipation symptoms before intake in the RB group was significantly longer compared with controls (3.7 vs 0.4 years, P < 0.001). By 24 months, the cumulative percentage of children achieving at least 1 period of successful outcome was significantly higher in the control group compared with RB population (73% vs 24%, P < 0.001). Multivariate analysis revealed that younger age ( P = 0.001, odds ratio 0.87) and shorter duration of constipation before RB ( P = 0.03, odds ratio 0.45) were significant predictors of successful outcome. Conclusions: Only one-quarter of patients with severe constipation achieved successful outcome during 2-year follow-up. Younger age and shorter duration of constipation at time of biopsy were predictors of successful outcomes, emphasizing the importance of early diagnosis and initiation of treatment in this population.